2019
DOI: 10.1126/scitranslmed.aav5341
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hyperglycolysis in mesothelial cells prevents peritoneal fibrosis

Abstract: Progressive peritoneal fibrosis affects patients receiving peritoneal dialysis (PD) and has no reliable treatment. The mechanisms that initiate and sustain peritoneal fibrosis remain incompletely elucidated. To overcome these problems, we developed a strategy that prevents peritoneal fibrosis by suppressing PD-stimulated mesothelial-to-mesenchymal transition (MMT). We evaluated single-cell transcriptomes of mesothelial cells obtained from normal peritoneal biopsy and effluent from PD-treated patients. In cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
104
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(109 citation statements)
references
References 35 publications
5
104
0
Order By: Relevance
“…Metabolic reprogramming is emerging as a critical event in fibrogenic activation across different tissue types. [4,5,35,36] Therefore, we examined the effects of CM272 on oxygen consumption rate (OCR; a representation of mitochondrial activity) and the extracellular acidification rate (ECAR; a surrogate for glycolytic rate) in LX2 cells treated with TGF. As recently reported we found that TGF reduced OCR and increased ECAR, [36] however these effects were attenuated by CM272 ( Fig.…”
Section: Mechanisms Of the Inhibitory Effects Of Cm272 On Hepatic Myomentioning
confidence: 85%
“…Metabolic reprogramming is emerging as a critical event in fibrogenic activation across different tissue types. [4,5,35,36] Therefore, we examined the effects of CM272 on oxygen consumption rate (OCR; a representation of mitochondrial activity) and the extracellular acidification rate (ECAR; a surrogate for glycolytic rate) in LX2 cells treated with TGF. As recently reported we found that TGF reduced OCR and increased ECAR, [36] however these effects were attenuated by CM272 ( Fig.…”
Section: Mechanisms Of the Inhibitory Effects Of Cm272 On Hepatic Myomentioning
confidence: 85%
“…Recent studies have suggested that TGF-β-driven activation of fibroblasts may involve accentuation of metabolic activity. TGF-β stimulation induces metabolic reprogramming in fibroblasts and accentuates glycolytic pathways (Si et al, 2019), inducing expression and activation of hexokinase-2 (Yin et al, 2019). Hexokinase-2 activation has been shown to stimulate myofibroblast conversion while also inducing ECM gene synthesis (Yin et al, 2019).…”
Section: Effects Of Tgf-βs On Fibroblastsmentioning
confidence: 99%
“…More recently we have also seen that metabolic reprograming plays an essential role in the differentiation and cell fate commitment of pluripotent stem cells 5 . Likewise there is also mounting evidence of a reprogramming of cellular metabolism in various forms of fibrosis [6][7][8] , including myofibroblast-like cells 8,9 in keloids 10 , hepatic 11,12 , lung 8 and perioteneal 13 fibrosis. Although TGF-β1 is a specific driver in many cases [11][12][13] , the molecular events underpinning these global changes remain ill-defined.…”
mentioning
confidence: 99%